1953
DOI: 10.1017/s0025315400011449
|View full text |Cite
|
Sign up to set email alerts
|

On The Biology Of Glossus Humanus (L.) (Isocardia Cor Lam.)

Abstract: Glossus humanus (L.), the only living representative of the genus, .is a large eulamellibranch living in Western European seas and the Mediterranean. Nicol (1951) has reviewed the geological history and geographical distribution of the species, but little is known of its structure and habitat. Specimens were obtained from the Clyde Sea Area by use of an Agassiz trawl in depths of over 5°m. in the channeljJetween the islands of Arran and Bute. Work on these specimens was carried out at the Marine Station, Millp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0
2

Year Published

1960
1960
2014
2014

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 58 publications
(31 citation statements)
references
References 18 publications
0
21
0
2
Order By: Relevance
“…The unusual abundance or size of Glossus humanus and its proximity to large bones at two sites (W1, W8) might point to its special adaptation to high sulphide concentrations. However, the only available study on the biology and diet of this taxon (Owen ), adapted to very soft and calm mud bottoms, does not support this hypothesis. Nassariidae, found at three sites (W1, W3, W20), and abundant in some cases, are scavengers that might have fed directly on the whale flesh, as observed in modern examples (Glover et al .…”
Section: Discussionmentioning
confidence: 92%
“…The unusual abundance or size of Glossus humanus and its proximity to large bones at two sites (W1, W8) might point to its special adaptation to high sulphide concentrations. However, the only available study on the biology and diet of this taxon (Owen ), adapted to very soft and calm mud bottoms, does not support this hypothesis. Nassariidae, found at three sites (W1, W3, W20), and abundant in some cases, are scavengers that might have fed directly on the whale flesh, as observed in modern examples (Glover et al .…”
Section: Discussionmentioning
confidence: 92%
“…40 (2) with longitudinal grooves and ridges. This feature was defined as the acceptance tract by Owen (1953), corresponds to the anterodorsal tract of Reid (1965), and is possibly homologous to Sorting Area 5 ('SA 5 ') of Purchon (1960). New character.…”
Section: Alimentary System Characters (Figs 16-18)mentioning
confidence: 99%
“…The diagnostic feature of this type of stomach is the extension of the major typhlosole and the intestinal groove into two caeca, one on the right side of the oesophageal orifice and one on the left. It has been suggested that this is typical of the majority of the Eulamellibranchia (Owen, 1953 ;Morton, 1958) but this is not correct. Of all the families of Eulamellibranchia which have been studied in this respect only about one half possess a stomach of Type V, the stomach in the remainder being of Type IV .…”
Section: Stomach Type Vmentioning
confidence: 99%